Efektivitas Pembelajaran Daring Di Masa Pandemi Covid-19 - Inne Nuriel Primestike; Qatrunnada Salsabila (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The purpose of this study was to identify obtaining information about the obstacles to the online teaching and learning process at home as a result of the COVID-19 pandemic. This research is entitled